Interplay of epigenetics and epistasis drives oral submucous fibrosis - Mohit Sharma; Smitha Sammith Shetty; Faisal Alhedyan; Raghu Radhakrishnan (Discover Applied Sciences)
Abstract Persistent injury to oral mucosa due to habitual quid chewing, resulting in the upregulation of inflammatory cytokines and consequential myofibroblastic persistence, emphasizes the role of epigenetic aberration in the pathogenesis of oral submucous fibrosis (OSF). However, there is a dearth of research on the role epistasis plays in the pathophysiology of OSF. Among the important epistatic interactions in the pathophysiology of OSF are those between Phosphatase and Tensin Homologue (PTEN) and Insulin-Like Growth Factor 1, Transforming Growth Factor-β (TGF-β), Cyclooxygenases, and lipoxygenases (LOX). Additionally, PTEN and Nuclear Factor Kappa B (NF-κB) have an epistatic relationship that is particularly mediated by the p65 subunit of NF-κB. Given the importance of epigenetic modification in the pathogenesis of OSF, the potential use of DNA methyltransferase and Histone deacetylase inhibitors as a therapeutic option holds promise. Another in vivo epigenetic therapeutic option for treating OSF is using stimulatory microRNAs against antifibrotic genes and inhibitory microRNAs against profibrotic genes. This review aims to connect numerous epigenetic and epistatic components to the mechanism of OSF. A better understanding of the disease process may provide OSF management with newer therapeutic options. Graphical Abstract